Integrasi Paket Modul Data Cleansing Pada Aplikasi DQM Tools Menggunakan Open Source Tools - Rahadian Aldi Nugroho (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2022)
Data is a source of information on decision making. Data with good quality can produce decisions that can make a company successful. To ensure that the existing data is of good quality, the company can perform data quality management. Data quality management is a set of activities carried out to ensure that the data to be used and processed is of good quality. In data quality management, there are a series of strategies, namely data profiling, data cleansing, data monitoring, and data integration. Data cleansing is the process of converting low-quality data into high-quality data. Data Quality Management Tools (DQM Tools) is an application that can perform the data cleansing process. In the DQM Tools application, there are also several cleansing modules that have not been installed and have not been integrated between the modules. In this study, we will discuss the adjustments made so that the existing and new data cleansing modules can be installed and integrated into the DQM Tools application. This research was also conducted using the Iterative Incremental method. The results obtained in this study are integrated and installed the data cleansing module in the DQM Tools application. The conclusion that can be drawn from this research is that the module can be integrated by adjusting the business processes in the application. The results of this study are very helpful for users when using the DQM Tools application when they want to do data cleansing.